2018
DOI: 10.1177/1120700018813224
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes of acetabular revision with the Delta Revision TT cup

Abstract: Introduction: This study evaluates mid-term results of acetabular revision using a hemispherical acetabular cup in Trabecular Titanium with a cage construct. Methods: We reviewed 36 acetabular revisions performed with the Delta Revision TT cup in 34 patients (mean age = 75, range: 45-92 years). Acetabular defect types (Paprosky classification) included (1) 2B (n = 5), (2) 2C (n = 7), (3) 3A (n = 15), and (4) 3B (n = 9). Morcellised bone allografts were used in 24 cases, and synthetic bone used in 11. Outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Perticarini et al [13] found that 99.3% of the Delta TT cups used in 134 THA and 8 revision cases were radiographically stable at a mean follow-up period of 72.7 months; dislocation occurred in two cases, aseptic loosening in one patient. Munegato et al [15] described good clinical and radiographic results at short-to mid-term follow-up (mean period 39.8 months), with three cases of dislocation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Perticarini et al [13] found that 99.3% of the Delta TT cups used in 134 THA and 8 revision cases were radiographically stable at a mean follow-up period of 72.7 months; dislocation occurred in two cases, aseptic loosening in one patient. Munegato et al [15] described good clinical and radiographic results at short-to mid-term follow-up (mean period 39.8 months), with three cases of dislocation.…”
Section: Discussionmentioning
confidence: 97%
“…Recent clinical studies of 3D-printed cups have shown good outcomes [12][13][14][15]; however, no laboratory studies have previously characterized the whole components. On the contrary, several studies have investigated the biocompatibility and suitability of 3D-printing to produce porous structure for orthopaedic applications, but these were limited to cylindrical or cubic specimens [7,[16][17][18][19][20][21][22][23][24][25][26],…”
Section: Introductionmentioning
confidence: 99%
“…This is a substantial improvement over the cementation of a polyethylene cup into a revision cup, such as the Burch Schneider ring. The modularity of the applied MUTARS ® RS CUP system makes it possible to correct the inlay position, the center of hip rotation and to minimize the risk of dislocation [ 19 , 20 ] (Fig. 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This titanium implant has shown excellent osseous integration in animal models and has been used successfully in revision hip surgery. 1,3,16,[30][31][32][33] It is composed of a 3D hexagonal lattice of titanium with high porosity (Figure 4a), manufactured using electron beam melting and designed to mimic cancellous bone. The highly porous titanium optimizes press-fit in bone due to high friction.…”
Section: Methodsmentioning
confidence: 99%